RECOGNIZING THE GREATNESS OF THE CREATOR: THE EDUCATIONAL MESSAGE OF SURAH AL-MULK VERSES 1-5 - Rifal Aditya; Intan Ayu Saputri; Miranda; Abdul Rajab Nasution; Fauziah Nur Ariza (Journal Informatic, Education and Management (JIEM), 2026)
This study discusses the educational messages contained in Surah Al-Mulk verses 1–5, focusing on introducing the greatness of Allah as the Creator. The research employs a library research method with a content analysis approach by examining the Qur'an, several Qur'anic commentaries, including Tafsir Ibn Kathir, Tafsir Al-Munir by Wahbah Az- Zuhaili , Tafsir Al-Misbah by M. Quraish Shihab, Tafsir Al-Qurtubi, and Tafsir Al- Jalalayn , as well as Hadith and other relevant scholarly sources. The findings show that Surah Al-Mulk verses 1-5 contain many educational values ​​that are important to apply in everyday life. These verses teach that Allah has absolute authority over the entire universe, encouraging people to strengthen their faith and trust in Him. In addition, life and death are described as part of a process of education and a test so that human beings strive to perform their best deeds rather than merely increasing the number of their deeds. The surah also encourages people to observe the order and harmony of the universe as evidence of Allah's greatness, while fostering critical thinking, curiosity, and gratitude. These values ​​serve as an important foundation for Islamic education because they help shape learners who possess strong faith, good character, responsibility, and the ability to learn from every aspect of Allah's creation. Therefore, Surah Al-Mulk verses 1-5 can serve as one of the foundations for developing Islamic education that not only enhances knowledge but also builds character and strengthens the spiritual awareness of learners.